Habitat characteristic of Corbicula Fluminea at two different rivers in Southern Thailand - Zaween Najjah Mohamad Shamsul (2017)
Corbicula fluminea has been a traditional food for the locals from both Kelantan and in Southern Thailand. However, the ecology of C. fluminea has not been fully explored in Malaysia and also in Southern Thailand. C. fluminea were sampled in two different rivers at Southern Thailand; Pattani River and Saiburi River. The water quality parameters involved in this study are dissolved oxygen, pH, temperature and the nutrient analysis which is phosphate and nitrate. Water chemistry from both rivers were analysed to determine suitable waters for habitation. Both of this rivers have a suitable pH levels ranging from (6.53-6.7), temperature range (31-34ºC) and contain a sufficient dissolved oxygen (DO) in a range of (3.3-8.1 mg/L) for the C. fluminea to survive. C. fluminea were collected and measured its shell length. This species is most abundant in length size 11-20 mm. The highest density of C. Fluminea recorded at Pattani River, 369 clams per m2 while only 196 per mx2 at Saiburi River. The overexploitation by the villagers at Saiburi River has caused the densities of C. Fluminea differs significantly. The substrate type between these two rivers were also analysed; Pattani River has a sandy loam substrate while the substrate in Saiburi River is a loamy sand. The availibility of the phytoplankton were also identified in both rivers and overall there were 29 species from 22 different family in both rivers. This study shows that the densities of C. fluminea is likely to be influenced by the water quality rather than substrate types and also the phytoplankton availability.